HARMONIZATION OF NATIONAL LAWSWITH THEVIENNA CONVENTION 1961 ON DIPLOMATIC RELATIONS - R. Adi Prasetyo; Lina Hastuti1 (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Diplomatic mission has the immunity and privilege. But, international law distinguishes the public and private actions of a state. When the state takes a private action or a jurigestionis, then the state no longer has the immunity. As an example, the caseof the Brazilian Embassy in Indonesia which terminates a sudden employment contract with Indonesian employee without compensation. The act of providing employment or termination of employment is a private action. This study aims to answer the legal issues that arise about the immunity of diplomatic missionrelated to the state practices, and as a contribution to solving the problems that occur in society, especially for worker who works at foreign embassy. The type of the study was normative legal research or legal research. Arising ofthe legal issueagainst the immunity of diplomatic mission was related to the state practices, especially for worker who works at foreign embassy.